2013
DOI: 10.1113/jphysiol.2012.241760
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed energy metabolism and muscular dystrophy caused by pure creatine deficiency are reversible by creatine intake

Abstract: Key points• Creatine (Cr) plays an important role in muscle energy homeostasis as a substrate in the creatine kinase phosphoryl exchange reaction, but the consequences of creatine depletion are incompletely understood.• We assessed the morphological, metabolic and functional consequences of systemic creatine depletion on skeletal muscle in a mouse model with deficiency of an essential enzyme in the biosynthesis of creatine (AGAT −/− mice).• We show that Cr depletion leads to several metabolic abnormalities in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
88
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(92 citation statements)
references
References 107 publications
(160 reference statements)
3
88
1
Order By: Relevance
“…Mice deficient in the Cr-synthesizing enzyme arginine:gylcine amidinotransferase (AGAT −/− ) show increased mitochondrial enzyme activity in the muscle. Citrate synthase activity is increased in the AGAT −/− mice as well (Nabuurs et al 2013). The increase in mitochondrial activity and citrate synthase support the findings in this study that Cr deficiency increases the number of mitochondria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mice deficient in the Cr-synthesizing enzyme arginine:gylcine amidinotransferase (AGAT −/− ) show increased mitochondrial enzyme activity in the muscle. Citrate synthase activity is increased in the AGAT −/− mice as well (Nabuurs et al 2013). The increase in mitochondrial activity and citrate synthase support the findings in this study that Cr deficiency increases the number of mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Crt −/y mice show significant reductions in ATP both in this study and as shown previously (Russell et al 2014). AGAT deficient mice have reduced muscular ATP (Nabuurs et al 2013). CK knockout mice have ATP reductions during seizures and hypoxia (Kekelidze et al 2001); paradoxically double CK knockout (CK −/− ) mice do not have ATP reductions (in 't Zandt et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This GAA may then be phosphorylated to produce energy-rich P-GAA, which in turn can be used as a substrate by CK instead of PCr (Heerschap et al 2007). In contrast to the latter, mice with AGAT deficiency present with complete absence of creatine and GAA in all tissues of the body and, as would be expected, with a severe muscle phenotype associated with reduced muscle strength, muscle atrophy, decreased ATP and increased inorganic phosphate (Pi) levels (Nabuurs et al 2013). The latter situation results in significantly disturbed oxidative phosphorylation.…”
Section: Creatine and Cancermentioning
confidence: 99%
“…Mating, housing, and generation of mice were performed as described previously [18][19][20] (Methods in the online-only Data Supplement).…”
Section: Mouse Modelsmentioning
confidence: 99%